Desenvolvimento de aplicação para cidades inteligentes utilizando da plataforma FIWARE - Minatel, Refael Tury (Universidade Federal de São Carlos, 2025)
The accelerated growth of contemporary cities demands technological solutions that promote efficiency in the management of urban resources and services. In this context, Smart Cities use Information and Communication Technologies to transform data into effective decisions. This work investigates and demonstrates, through a practical approach, how the FIWARE platform can be applied in the development of Smart City applications. The main objective was to develop a functional prototype that simulates intelligent monitoring and control of an event hall, integrating IoT sensors (temperature, humidity, CO$_2$, occupancy) and actuators (air conditioner, exhaust fan, alarm) through FIWARE components: Orion Context Broker, IoT Agent JSON, and QuantumLeap. The methodology adopted applied research with a qualitative and exploratory approach, developing the system in a containerized environment with Docker and a web interface in React. The implemented system demonstrated adequate operation, with automation responding in less than 2 seconds, historical data visualization, and responsive interface. The work thoroughly documents the challenges faced (container configuration, CORS, component integration) and the solutions adopted, presents a comparative analysis with the InterSCity platform, and systematizes requirements and best practices for similar projects. The results demonstrate that FIWARE is a viable, robust, and suitable platform for developing Smart City solutions, provided its particularities are understood and appropriate configuration and integration practices are adopted. The main contributions include a replicable functional prototype, consolidated documentation of integration between FIWARE components, and critical analysis that complements the existing literature.
Development of an application for smart cities using the FIWARE platform
Keywords: Cidades inteligentes; FIWARE; Internet das coisas; Orion context broker; Automação; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO; 11. Cidades e Comunidades Sustentáveis